Community structure of coral reef zooplankton in Isla del Coco National Park, a natural World Heritage site in the Eastern Tropical Pacific - Esquivel-Garrote, Octavio (2020)
Introduction: Zooplankton is a major link between primary producers and the following trophic levels, and in coral reefs they represent an energy source for corals and involve complex assemblies integrating a wide variety of species form different functional groups. Objective: To define interannual changes in zooplankton assemblies in coral reefs of Isla del Coco. Methods: Three coral reefs system were sampled. Two or three samples were taken by surface horizontal trawls in each coral reef from 2009 to 2012, using conical zooplankton nets of 200 and 500 µm mesh sizes at different times of the day. Physical and chemical variables were measured before zooplankton sampling. Results: We identified 24 taxonomic groups of macrozooplankton and 22 of mesozooplankton. Copepods were the most abundant taxa (87.1%) of the total abundance of mesozooplankton and macrozooplakton (58.9%); however, chaetognaths (35.6%) exceeded copepods (35.4%) in abundance in macrozooplankton samples during 2011. Mesozooplankton samples showed higher abundance (68753.2±9123.2 ind m-3) and biomass (85.14±11.3 mg DW m-3) than macrozooplankton samples (4454.9±751.0 ind m-3, 22.8±3.8 mg DW m-3). The interannual macrozooplankton community structure did not change significantly (ANOVA, p=0.368), but did change for mesozooplankton (ANOVA, p=0.001). Variations in physical and chemical variables influenced the community structure for both meso and macrozooplankton, increasing or decreasing organism abundance. Conclusions: Coral reef zooplankton of Isla del Coco resembles that of other coral reefs under the influence of oceanic conditions, with a fauna formed mainly by calanoid copepods, chaetognaths and appendicularians, and depending on oceanographic conditions, the abundance of these groups can change.